Actualization of Linguodidactic Techniques in Teaching a Foreign Language to Students of Higher Educational Institutions - Soroka, Tetiana (Didactica Danubiensis, 2024)
Literature as a branch of human knowledge and a foreign language as a cognitive phenomenon have an expressed synthetic character, combining the possibility of describing the sensory perception of the surrounding reality with a way of conveying abstract ideas of various levels of complexity. Being both a goal and a means of learning, a foreign language in cognitive terms allows a person to look at the world through the prism of a foreign language and a foreign cultural worldview, thereby ensuring the formation of a so-called secondary linguistic personality. Modern linguodidactics considers teaching a foreign language as a complex task, the structure of which genetically includes, in addition to the linguistic proper, pragmatic (academic), developmental (cognitive) and educational (socio-cultural) aspects. The use of extralinguistic aspects in the educational process, associated with the study of socio-cultural characteristics and the application of professional competencies, as well as the realization of a student's scientific interests contribute to the actualization of the pragmatic aspect. It is proved that interest in the culture of the studied language increases motivation to learn a foreign language, in turn, contributing to the activation of cognitive processes of a purely linguistic nature and positively influencing the formation of a student's professional and linguistic personality. Techniques that activate the cognitive processes of students should be characterized by interactivity and be aimed at updating their subjective and professional experience. Research work in a foreign language, participation in international seminars and conferences, striving for discoveries and focus on results can create a favorable environment for the natural acquisition of conversational and academic skills in the field of learning a foreign language in parallel with the development of academic and cognitive abilities of a student.